Theory Summary - Rosenfeld, Rogerio [UNESP] (Elsevier B.V., 2015)
I provide a brief summary of the theory talks that were presented at X Simposio Latinoamericano de Fisica de Altas Energias (SILAFAE).
Keywords: Theory